Antiangiogenic Effect of Alkaloids. (21st April 2019) - Alasvand, Masoud; Assadollahi, Vahideh; Ambra, Roberto; Hedayati, Ehsan; Kooti, Wesam; Peluso, Ilaria
Abstract : Alkaloids are among the natural phytochemicals contained in functional foods and nutraceuticals and have been suggested for the prevention and/or management of oxidative stress and inflammation-mediated diseases. In this review, we aimed to describe the effects of alkaloids in angiogenesis, the process playing a crucial role in tumor growth and invasion, whereby new vessels form. Antiangiogenic compounds including herbal ingredients, nonherbal alkaloids, and microRNAs can be used for the control and treatment of cancers. Several lines of evidence indicate that alkaloid-rich plants have several interesting features that effectively inhibit angiogenesis. In this review, we present valuable data on commonly used alkaloid substances as potential angiogenic inhibitors. Different herbal and nonherbal ingredients, introduced as antiangiogenesis agents, and their role in angiogenesis-dependent diseases are reviewed. Studies indicate that angiogenesis suppression is exerted through several mechanisms; however, further investigations are required to elucidate their precise molecular and cellular mechanisms, as well as potential side effects.